Possibility not Difficulty: Difficult Knowledge in K-12 classrooms as Opportunities for Renegotiating Relationships with Indigenous Knowledge - Douglas, Velta; Purton, Fiona; Bascuñán, Daniela (Alberta Journal of Educational Research, 2020)
Indigenous perspectives and knowledges have been rendered “difficult” to teach and learn due to settler-colonial norms that are naturalized in Ontario’s public K-12 education system. We explore how we as educators and teachers with diverse populations of students critically engage pedagogy and knowledge to take up Indigenous perspectives and knowledges in classrooms in ethical ways. Using practitioner inquiry, we draw on our classroom experiences to explore how students engage with Indigenous perspectives and knowledges and our relationships as people who relate to this land in different ways—as settlers, newcomers, and original caretakers. Students perceive our pedagogical interventions not as difficult, but as a disruption from settler colonialism, that can be navigated through. We argue that not only is there nothing inherently difficult about Indigenous perspectives and knowledges, but also that students enter into difficulty as possibility. Although students experience disruptions, they seek out ways to renegotiate their relationships to settler colonialism and Indigenous perspectives and knowledges and come to new understandings about their contexts. We argue that examining these disruptions as teacher researchers in our classrooms adds nuance to conversations about revealing how settler colonialism functions and complexity to the task of taking up Indigenous perspectives and knowledges in K-12 classrooms. Keywords: Indigenous perspectives, settler colonialism, difficult knowledge, pedagogy, practitioner inquiry Les perspectives et les connaissances autochtones sont devenues des matières « difficiles » à enseigner en raison des normes des colonisateurs qui sont naturalisées au sein du système d’éducation publique de la maternelle à la 12e année en Ontario. Nous explorons dans quelle mesure nous, en tant qu’enseignantes qui travaillons avec des populations diverses d’élèves, adoptons une approche critique et réfléchie à la pédagogie et aux connaissances de sorte à intégrer les perspectives et les connaissances autochtones en classe de façon éthique. Reposant sur une enquête auprès de praticiens, nous puisons dans nos expériences en classe pour explorer la réaction des élèves aux perspectives et aux connaissances autochtones ainsi qu’à nos rapports en tant que personnes qui entretiennent des liens différents avec ce territoire—en tant que colonisateurs, nouveaux arrivés ou premiers gardiens. Les élèves ne perçoivent pas nos interventions pédagogiques comme étant difficiles, mais comme une perturbation du colonialisme de peuplement à travers laquelle il est possible de naviguer. Nous affirmons que non seulement les perspectives et les connaissances autochtones ne sont pas difficiles en soi, mais en plus, les élèves abordent la difficulté comme une possibilité. Les élèves vivent des perturbations, cherchent des façons de renégocier leurs rapports au colonialisme de peuplement et aux perspectives et connaissances autochtones, et ils acquièrent une nouvelle compréhension de leurs contextes. Nous affirmons qu’en examinant ces perturbations comme chercheurs-enseignants dans nos salles de classes, nous ajoutons une nuance aux conversations sur le fonctionnement du colonialisme de peuplement et rendons plus complexe la tâche d’adopter des perspectives et des connaissances dans les classes M-12. Mots clés : Perspectives autochtones, colonialisme de peuplement, connaissances difficiles, pédagogie, enquête auprès des praticiens